Africa Gas Initiative : Volume 5. Cote d'Ivoire - World Bank (Washington, DC, 2014)
The Africa Gas Initiative (AGI) has been established by the Oil and Gas Division of the World Bank, to promote the utilization of natural gas in Sub-Saharan Africa. The study focuses on coastal countries - Angola, Cameroon, Congo, Cote d'Ivoire, and Gabon - along the West African coastline, and the Gulf of Guinea, where most of the region's gas reserves are located, and where significant proportions of the gas produced, is being wasted through flaring, or venting. Thus, the study's goal is to end gas flaring, by developing indigenous natural gas resources for local markets, and export, achieving economic benefits from gas substitution - through reduced imports, or increased exports of oil products - and, by improving environmental conditions at the local, and global levels. Under the AGI, technical assistance with regard to institutional, and regulatory framework was conducted in Cameroon, and Cote d'Ivoire, and, additionally, analysis of current petroleum fiscal legislation was undertaken, to review the profitability of gas field development from the investors' point of view. This analysis enabled recommendations to respective governments, to introduce required changes in their petroleum laws. Recommendations further include incentives to develop activities, particularly through rational price structures, removal of subsidies as the landed cost of liquefied petroleum gas (LPG) is progressively reduced, and fair competitive procedures, govern market accessibility.